Homozygous and Heterozygous Nuclear Lamin A p.R582C Mutation: Different Lipodystrophic Phenotypes in the Same Kindred - Montenegro, Renan Magalhães; Costa-Riquetto, Aline Dantas; Fernandes, Virgínia Oliveira; Montenegro, Ana Paula Dias Rangel; Santana, Lucas Santos de; Jorge, Alexander Augusto de Lima; Karbage, Lia Beatriz de Azevedo Souza; Aguiar, Lindenberg Barbosa; Carvalho, Francisco Herlânio Costa; Teles, Milena Gurgel; d'Alva, Catarina Brasil (Frontiers in Endocrinology, 2018)
Background. Dunnigan-type familial partial lipodystrophy, a rare autosomal dominant disease caused by heterozygous missense mutations in LMNA gene presents regional loss of subcutaneous adipose tissue from puberty. But the same mutation may present huge clinical heterogeneity. Methods. We report 4 patients from the same family with p.R582C LMNA mutation, 3 of them with homozygous and 1 with heterozygous state, presenting 3 distinct lipodystrophic phenotypes and we compare their clinical and metabolic features. Results. Case descriptions: The proband: a 12 year-old girl who developed selective loss of subcutaneous fat and hypertriglyceridemia, was diagnosed with lipodystrophy. In adult life, she presented severe subcutaneous fat atrophy in limbs and abdomen with a remarkable dorsocervical fat accumulation, and diabetes at age 23 (BMI 20.5 Kg/m²). Proband’s sister: phenotypically normal 8 year-old girl with hypertriglyceridemia who developed progressive features of partial lipodystrophy from 11 years-old and diabetes at age 22 (BMI 20.7 Kg/m²). Proband’s mother: at age 32 revealed a severe generalized lipodystrophic phenotype (BMI 17.2 Kg/m²) and she developed diabetes at age 24, kidney failure at age 41 and deceased at 42 years-old due to diabetic complications. Proband´s father: 50 years-old man with abdominal fat concentration without lipoatrophy (BMI 24.9 Kg/m²). The family´s molecular study, by massively parallel sequencing using a plataform of genes related to genetic lipodystrophies, followed by Sanger sequencing, revealed the transversion c.1744C>T at exon 11 of the LMNA gene (p.R582C) in homozygous state (mother and daughters) and in heterozygous state (father). Conclusion. The p.R582C LMNA mutation in heterozygous resulted in an uncertain phenotype and in homozygous caused severe lipodystrophic syndromes with phenotypic differences, as the finding of partial or generalized lipodystophy. That familial lipodystrophy linked to mutations in this gene is a disease of great clinical heterogeneity.